Diagnosis Penyakit THT Menggunakan Metode Fuzzy Tsukamoto Berbasis Android - Fahmiyanto Ekajaya; Nurul Hidayat; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
During this time the diagnosis of the disease always relies on clinical or laboratory estimates. Where with it many found deficiencies that resulted in losses for the patient in managing time. Based on the inventory data and the number of requests, it is designed a decision support system using the method fuzzy tsukamoto.In the diagnosis system of THT diseases with android based The demand variable consists of two fuzzy set, namely: DOWN, and NAIK, inventory variable consists of two fuzzy set, : LITTLE, and MANY, while the production variable consists of two fuzzy sets namely: REDUCE, and ADDED. The calculation of accuracy in this study was not separated based on each disease but accuracy for the whole disease and resulted in an accuracy of 93.75%